An interlaboratory study of TEX86 and BIT analysis of sediments, extracts, and standard mixtures. (20th December 2013) - Schouten, Stefan; Hopmans, Ellen C.; Rosell‐Melé, Antoni; Pearson, Ann; Adam, Pierre; Bauersachs, Thorsten; Bard, Edouard; Bernasconi, Stefano M.; Bianchi, Thomas S.; Brocks, Jochen J.; Carlson, Laura Truxal; Castañeda, Isla S.; et al.
<x xml:space="preserve">Abstract</x> [2] Two commonly used proxies based on the distribution of glycerol dialkyl glycerol tetraethers (GDGTs) are the TEX86 (TetraEther indeX of 86 carbon atoms) paleothermometer for sea surface temperature reconstructions and the BIT (Branched Isoprenoid Tetraether) index for reconstructing soil organic matter input to the ocean. An initial round‐robin study of two sediment extracts, in which 15 laboratories participated, showed relatively consistent TEX86 values (reproducibility ±3–4°C when translated to temperature) but a large spread in BIT measurements (reproducibility ±0.41 on a scale of 0–1). Here we report results of a second round‐robin study with 35 laboratories in which three sediments, one sediment extract, and two mixtures of pure, isolated GDGTs were analyzed. The results for TEX86 and BIT index showed improvement compared to the previous round‐robin study. The reproducibility, indicating interlaboratory variation, of TEX86 values ranged from 1.3 to 3.0°C when translated to temperature. These results are similar to those of other temperature proxies used in paleoceanography. Comparison of the results obtained from one of the three sediments showed that TEX86 and BIT indices are not significantly affected by interlaboratory differences in sediment extraction techniques. BIT values of the sediments and extracts were at the extremes of the index with values close to 0 or 1, and showed good reproducibility (ranging from 0.013 to 0.042). However, the measured BIT values for the two GDGT mixtures, with known molar ratios of crenarchaeol and branched GDGTs, had intermediate BIT values and showed poor reproducibility and a large overestimation of the "true" (i.e., molar‐based) BIT index. The latter is likely due to, among other factors, the higher mass spectrometric response of branched GDGTs compared to crenarchaeol, which also varies among mass spectrometers. Correction for this different mass spectrometric response showed a considerable improvement in the reproducibility of BIT index measurements among laboratories, as well as a substantially improved estimation of molar‐based BIT values. This suggests that standard mixtures should be used in order to obtain consistent, and molar‐based, BIT values.